THE THEORETICAL-METHODOLOGICAL BASES OF CLASSIFICATION OF RIGHTS AND GUARANTEES OF SCIENTIFIC-PEDAGOGICAL WORKERS - Petryk O.L. (Pressing Problems of Public Administration, 2015)
The main scientific approaches to defining the concepts “rights” and “guarantees” have been investigated. The scientists` basic views regarding the possible grouping of human and citizens` rights and guarantees have been highlighted. The classification of rights and guarantees of scientific-pedagogical workers as special participants of the educational process has been done.